In Vitro and In Vivo Effects of Silver Nanoparticles Biosynthesized By Serratia Marcescens - Khawlah Jebur Khalaf (Journal of Global Pharma Technology, 2018)
Biosynthesis of silver nanoparticles by Serratia marcescens was demonstrated using the supernatant for extracellular biosynthesis. The formation of AgNPs was characterized by UV-Vis spectrophotometry, atomic force microscopic (AFM) and fourier transform infrared spectroscopy (FTIR).Antimicrobial activity of silver nanoparticles was performed by use well diffusion method and show that these AgNPs can be used as growth inhibitors against pathogenic isolates: Salmonella sp. , Staphylococcus aureus. Staphylococcus epidermedis, E. coli, Klebsiella sp, Candida albicans .Antibiotic susceptibility of Salmonella sp. was determed by used disk diffusion method and found the most susceptible for amoxicillin, chloramphenicol, azithromycin, ampicillin and cefotaxime and resistance to flurmequine neomycin and colistin. The present study was designed to assess the effect of silver nanoparticles wich synthesized by serratia marcescens in modulating the salmonellosis in BALB/C mice. we found that in vivo the histological study for liver it was damage when compared with mice's liver treated with antibiotic (amoxicillin ) .Keywords: Serratia marcescens, silver nanoparticles, pathogenic bacteria, liver.